2019
DOI: 10.1186/s40658-019-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quantitative [I-123] mIBG SPECT/CT in a phantom and in patients with neuroblastoma

Abstract: Purpose:To determine the accuracy of quantitative SPECT, intersystem and interpatient standardized uptake value (SUV) calculation consistency for a manufacturerindependent quantitative SPECT/CT reconstruction algorithm, and the range of SUVs of normal and neoplastic tissue. Methods: A NEMA body phantom with 6 spheres (ranging 10-37 mm) was filled with a known activity-to-volume ratio and used to determine the contrast recovery coefficient (CRC) for each visible sphere, and the measured SUV accuracy of those sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The author reported an activity quantification error of 35.0% for the kidney, when no compensation for PVE was applied. Brady et al [ 12 ] reported 123 I activity quantification errors of 10.0% for spheres with volumes ranging between 5.8 mL and 29.0 mL.…”
Section: Quantificationmentioning
confidence: 99%
“…The author reported an activity quantification error of 35.0% for the kidney, when no compensation for PVE was applied. Brady et al [ 12 ] reported 123 I activity quantification errors of 10.0% for spheres with volumes ranging between 5.8 mL and 29.0 mL.…”
Section: Quantificationmentioning
confidence: 99%
“…The SUV estimated on the SPECT/CT dataset can be valuable to monitor changes in the mIBG avidity of the primary tumor after chemotherapy[ 29 ] [ Figure 4 ].…”
Section: I-meta-iodobenzylguanidine Scan To Assess Response To Induction Chemotherapymentioning
confidence: 99%
“…High-energy (HE) collimators with thicker septa are needed when imaging 131 I due to the relatively high primary photon energy of 364.5 keV, used for imaging, and because of the otherwise high septal scatter and penetration from the emission of the 636.9 keV and 722.9 keV photons (11). However, 123 I imaging can be performed with either a low energy high resolution (LEHR) or a medium energy (ME) collimator (12)(13)(14). The ME collimator reduces the septal penetration and scatter from the higher-energy photons of 123 I, resulting in improved image contrast and more accurate activity quantification.…”
Section: Introductionmentioning
confidence: 99%